ESTUDO DAS MANIFESTAÇÕES DA RELIGIOSIDADE AFRO-BRASILEIRA NO CENTRO DE UMBANDA “THSARA UNIVERSALISTA DE UMBANDA REINO DE CIGANOS”– SANTIAGO/RS - Oliveira, Graciela P.; Narvaes, Andréa B. (Salão do Conhecimento, 2013)
Resumo